Hubungan Pengetahuan dan Kepatuhan Penerapan Proteksi Radiasi: Studi pada Mahasiswa Praktik Klinik Jurusan Teknik Radiodiagnostik dan Radioterapi, Poltekkes Kemenkes Semarang - Sulistiyadi, Akhmad Haris; Abimanyu, Bagus; Kartikasari, Yeti; Isnoviasih, Susi Tri (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: Radiation protection is very important for patient and personnel safety in radiology services. It has been given in the college through classical lectures, including in Radiodiagnostic and Radiotherapy Department Poltekkes Kemenkes Semarang. The studentâ€™s knowledge is routinely evaluated but their compliance in the clinical activities has never been specifically observed. This study aims to find out the relationship between knowledge toward compliance of the application of radiation protection on clinical practice students.Methods: This is quantitative research with a cross-sectional design. Research was conducted on 90 second-year clinical internship students of the Radiodiagnostic and Radiotherapy Department. The level of knowledge was measured by written test, while the level of compliance was observed by clinical observation. The affecting factors are investigated through indepth interview. Data were analyzed by Spearman Rank Correlation.Results: The knowledge levels among the students were "excellentâ€ (18%), "good" (68%), and "fair" (14%). The radiation protection compliance levels were "good" (73%) and "very good" (27%). There was a significant relationship between radiation protection knowledge level toward radiation protection compliance (p value <0.05). The strength of the relationship was low (coefficient interval = 0.257).Â Conclusions: There was a relationship between knowledge and the level of compliance, but it was not the only influencing factor. The environment tends to have an effect on the level of compliance. Radiographers and clinical instructors should be good role model in applying radiation protection.